The Chemical Environment at Maturation Stage in Pinus spp. Somatic Embryogenesis: Implications in the Polyamine Profile of Somatic Embryos and Morphological Characteristics of the Developed Plantlets - do Nascimento, Antonia Maiara Marques; Polesi, Luiza Giacomolli; Back, Franklin Panato; Steiner, Neusa; Guerra, Miguel Pedro; Castander-Olarieta, Ander; Moncaleán, Paloma; Montalbán, Itziar Aurora (Frontiers in Plant Science, 2021)
Changes in the chemical environment at maturation stage in Pinus spp. somatic embryogenesis will be a determinant factor in the conversion of somatic embryos to plantlets. Furthermore, the study of biochemical and morphological aspects of the somatic embryos could enable the improvement of somatic embryogenesis in Pinus spp. In the present work, the influence of different amino acid combinations, carbohydrate sources and concentrations at the maturation stage of P. radiata D. Don and P. halepensis Mill. was analyzed. In P. radiata, the maturation medium supplemented with 175 mM of sucrose and an increase in the amino acid mixture (1100 mgL-1 of L-glutamine, 1050 mgL-1 of L-asparagine, 350 mgL-1 of L-arginine and 35 mgL-1 of L-proline) promoted bigger embryos, with a larger stem diameter and an increase in the number of roots in the germinated somatic embryos, improving the acclimatization success of this species. In P. halepensis the maturation medium supplemented with 175 mM of maltose improved the germination of somatic embryos. The increase in the amount of amino acids in the maturation medium increased the levels of putrescine in the germinated somatic embryos of P. halepensis. We detected significant differences in the amount of polyamines between somatic plantlets of P. radiata and P. halepensis; putrescine was less abundant in both species. For the first time in P. radiata and P. halepensis somatic embryogenesis, we detected the presence of cadaverine, and its concentration changed according to the species.